Alcohol and Cancer Proceedings of the Third International Conference (Advances in Experimental Medicine and Biology,, 2018)
Following the Third Alcohol and Cancer Conference, this volume compiles the most up-to-date research on the role of alcohol consumption in carcinogenesis, from epidemiology to pathology metabolism and stem cells. More specifically, it delves into the effects of alcohol consumption and thyroid cancer, CD133+ progenitor cells, carcinogenic iron accumulation, developmental morphogens, and cancer-inducing epigenetic changes. Alcohol and Cancer: Proceedings of the Third International Conference is a timely update to Biological Basis of Alcohol-Induced Cancer, which followed the Second Alcohol and Cancer Conference, compiling cutting-edge research from graduate students, young scientists, and researchers. It is ideal for graduate students and researchers in oncology, hepatology, epigenetics, and alcohol consumption.